Recent projects and initiatives at Toyota Archives. Issue 1 (January 2018) - Hasegawa, Takeshi
Abstract : Toyota Motor Corporation (TMC) celebrated its 75th anniversary in 2012. For TMC, rapid and large-scale growth of its global business operations has required the provision of historical information to a wide variety of global stakeholders. This paper describes how the TMC Archives Group has contributed to responding to this requirement in recent years. It introduces TMC and the TMC Archives Group which sits within the Corporate Citizenship Division (Social Contribution Division). Three core initiatives and projects within the Archives are presented: the production of the company history "75 Years of TOYOTA" at a time of company and financial crisis (2008 to 2011); using "75 Years of TOYOTA" for TMC employees; and the Museums project. The last part of the article notes how Archives Group will develop to meet future challenges while serving the vision of the company in the continuously changing business environment, of which digitalization and globalization are the two pivotal elements towards the future.